2012
DOI: 10.5194/nhess-12-575-2012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pre-earthquake ionospheric anomalies before the global <i>M</i> = 7.0+ earthquakes in 2010

Abstract: Abstract. The pre-earthquake ionospheric anomalies that occurred before the global M = 7.0+ earthquakes in 2010 are investigated using the total electron content (TEC) from the global ionosphere map (GIM). We analyze the possible causes of the ionospheric anomalies based on the space environment and magnetic field status. Results show that some anomalies are related to the earthquakes. By analyzing the time of occurrence, duration, and spatial distribution of these ionospheric anomalies, a number of new conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 17 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…The results showed that significant positive anomalies in the ionospheric electron density profile could be detected before the earthquake. Yao et al (2012b) investigate the unusual ionospheric total electron content (TEC) variations which occurred before the global M = 7.0+ earthquakes in 2010, and confirmed that the earthquake-related ionospheric anomalies discussed in the paper occurred 0-2 days before the associated earthquakes and in the afternoon to sunset. Yizengaw et al (2005) To compensate for the lack of GNSS tracking stations in marine areas, researchers used altimetry satellite data to directly access TEC trends over the global ocean (Dumont et al, 2009;Fu et al, 1994;Jee et al, 2004).…”
Section: Published By Copernicus Publications On Behalf Of the Europesupporting
confidence: 53%
“…The results showed that significant positive anomalies in the ionospheric electron density profile could be detected before the earthquake. Yao et al (2012b) investigate the unusual ionospheric total electron content (TEC) variations which occurred before the global M = 7.0+ earthquakes in 2010, and confirmed that the earthquake-related ionospheric anomalies discussed in the paper occurred 0-2 days before the associated earthquakes and in the afternoon to sunset. Yizengaw et al (2005) To compensate for the lack of GNSS tracking stations in marine areas, researchers used altimetry satellite data to directly access TEC trends over the global ocean (Dumont et al, 2009;Fu et al, 1994;Jee et al, 2004).…”
Section: Published By Copernicus Publications On Behalf Of the Europesupporting
confidence: 53%
“…After the work on the Christchurch precursor reports was complete, a paper appeared (Yao et al, 2012), which used data from the Global Navigation Satellite System (GPS) to pinpoint ionospheric precursors for the September event. The paper also reported similar geomagnetic precursors.…”
Section: Methodsmentioning
confidence: 99%
“…4. Lost pet data for Christchurch, with ionospheric data superimposed (Yao et al, 2012). The data from The Press are from pets lost at least one day prior.…”
Section: Lost/found Petsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the application, for which Bernese v5.0 academic software was used, approximate coordinates were calculated with PPP (Yildirim et al, 2013). The approximate coordinates were calculated by using the satellite-receiver time er- rors generated in 5 min intervals by IGS, in addition to the code and phase measurements of the CORS-TR stations.…”
Section: Determining the Seismic Origin Positional Variationmentioning
confidence: 99%